The electronics companion : devices and circuits for physicists and engineers - Fischer-Cripps, Anthony C. (Boca Raton, Florida : CRC Press, 2015)
Updated and expanded with new topics, The Electronics Companion: Devices and Circuits for Physicists and Engineers, 2nd Edition presents a full course in introductory electronics using a unique and educational presentation technique that is the signature style of the author$1 (Bs companion books. This concise yet detailed book covers introductory electrical principles (DC and AC circuits), the physics of electronics components, circuits involving diodes and transistors, transistors amplifiers, filtering, operational amplifiers, digital electronics, transformers, instrumentation, and power supplies. A Convenient, Student-Friendly Format Rich with Diagrams and Clear Explanations The level of coverage is introductory but at enough depth to enable students to undertake simple circuit design and construction. The book includes tutorial problems and a comprehensive set of laboratory experiments requiring conventional components and test equipment.s
Electricity -- DC Circuits -- AC Circuits -- Diodes -- Bipolar junction transistor -- Common emitter amplifier -- Input/Output impedance -- Field effect transistor -- High frequency -- Power amplifiers -- Transients -- Digital electronics -- Operational amplifiers -- Transformers -- Power supplies -- Instrumentation -- Laboratory.
Includes index.
Keywords: ELECTRONICS